The Respond of Insurgent Movement in Southern Thailand Toward Cebtral Thai Government. - Adul Leesen (HI 14 UMY 034, 2014)
Currently, the unrest situations in Southern Thailand have been increasing since 2002 until nowadays, several aspects which have been criticizing to every situation in positive and negative. Meanwhile, The government of Thailand is attempting to open the negotiation process with the insurgent groups and operation the suitable policies to the Southern area in order to solve the problem. Some insurgent groups in Southern Province are not believing with Thai government to open peace process that called â€œradical insurgentâ€ because they want to create the Pattani Islamic state as the past time. Moreover, the new intellectual groups called â€œmoderate insurgentâ€ who still believe that the violence could not implemented as well but the Muslim people in Southern Thailand must participate into political solution in order to negotiate with Thailand. In this research, the writer use an extensive of relevant published materials, such as, books, journals, report, newsletters, official websites, and other resources on a wide variety of the topics related with the subject of the paper. The propose of this undergraduate thesis is to explain on how did the insurgent groups in Southern Thailand responds to central Thai government which because of nowadays several groups are conducting into the difference ways such peaceful ways and violence ways in order to gain their goals. ix